A novel method for slip prediction of walking biped robots - Hashlamon, Iyad; Gülhan, Mehmet Mert; Ayit, Orhan; Erbatur, Kemalettin (Robotica, 2015)
This paper proposes a new approach for slip prediction of walking biped robots. The slip prediction is a measurement-based and friction behavior-inspired approach. A measurement-based online algorithm is designed to estimate the Coulomb friction which is regarded as a slip threshold. To predict the slip, a safety margin is introduced in the negative vicinity of the estimated Coulomb friction. The estimation algorithm concludes that if the applied force is outside the safety margin, then the foot tends to slip. The proposed approach depends on the available type of measurements. Three options of measurements are discussed. Among them, the foot acceleration and ankle force measurements scenario is validated by experiments on the humanoid SURALP (Sabanci University Robotics Research Laboratory Platform). The results demonstrate the effectiveness of the proposedapproach for slip prediction and detection.
Keywords: Biped; Slip prediction; Slip detection; Friction; LIPM and CoM states estimation